A Ratiometric Fluorescence Probe for Selective Detection of ex vivo Methylglyoxal in Diabetic Mice. Issue 5 (11th May 2022) - Xie, Qunfang; Zhan, Yuanjin; Guo, Longhua; Hao, Huili; Shi, Xianai; Yang, Jianmin; Luo, Fang; Qiu, Bin; Lin, Zhenyu
Abstract: Accurate monitoring of methylglyoxal (MGO) at cell and living level was crucial to reveal its role in the pathogenesis of diabetes since MGO was closely related to diabetes. Herein, a ratiometric fluorescence strategy was constructed based on the capture probe 2, 3‐diaminonaphthalene (DAN) for the specific detection of MGO. Compared to the fluorescent probes with a single emission wavelength, the ratiometric mode by monitoring two emissions can effectively avoid the interference from the biological background, and provided additional self‐calibration ability, which can realize accurate detection of MGO. The proposed method showed a good linear relationship in the range of 0–75 μm for MGO detection, and the limit of detection was 0.33 μm . DAN responded to MGO with good specificity and was successfully applied for detecting the ex vivo MGO level in plasma of KK−Ay mice as a type II diabetes model. Besides, the prepared DAN test strip can be visualized for rapid semi‐quantitative analysis of MGO using the naked eye. Furthermore, human skin fibroblasts and HeLa cells were utilized for exogenous MGO imaging, and ex vivo MGO imaging was performed on tissues of KK−Ay mice. All results indicated that the DAN‐based ratiometric fluorescence probe can be used as a potential method to detect the level of MGO, thus enabling indications for the occurrence of diabetes and its complications. Abstract : A ratiometric fluorescence probe with a large Stokes shift for specific detection of diabetes‐related methylglyoxal was obtained. 2, 3‐Diaminonaphthalene exhibited highly sensitive and anti‐interference ability for methylglyoxal detection by naked‐eye readout. This probe was thus capable of exogenous imaging methylglyoxal in living cells and ex vivo imaging methylglyoxal in the tissues of type II diabetes model mice.